1976
DOI: 10.3382/ps.0550685
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Constant Elevated Temperature and Diet on Egg Production and Shell Quality

Abstract: A total of 216 individually caged Single Comb White Leghorn pullets were divided into two equal groups and subjected to either a 21 ± 0.75° Cor a 32 ± 0.5° C. environmental temperature, both with 50% relative humidity. The birds in each group were fed either a typical corn-soy laying diet (15% prot., 2.8% Ca, 0.57% avail. P, 2,915 cal. M.E./gm. plus vitamins and minerals) or a "High Nutrient Density" (HND) diet (20% more of all nutrients except energy which was increased only 10%). The data collected during 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…It is then necessary to take additional care during the summer months to reduce negative effects on egg quality. The decrease in egg weight during July, although not significant, agrees with the results of De Andrade et al (1976) in high environmental temperatures.…”
Section: Discussionsupporting
confidence: 90%
“…It is then necessary to take additional care during the summer months to reduce negative effects on egg quality. The decrease in egg weight during July, although not significant, agrees with the results of De Andrade et al (1976) in high environmental temperatures.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the studies in laying hens have revealed detrimental effects of heat exposure on egg production and eggshell quality (Mueller, 1986;Smith, 1973Smith, , 1974de Andrade et al, 1974de Andrade et al, , 1976de Andrade et al, , 1977Wolfenson et al, 1978Wolfenson et al, , 1979. It has been variously suggested that decreased plasma concentration of calcium, respiratory alkalosis or blood flow redistribution might be responsible for these effects.…”
Section: Blood Flow To Abdominal Viscera and Skeletal Musclesmentioning
confidence: 95%
“…Also, the little work done in this area has investigated the interaction of heat stress and diet on laying hens rather than feed-restricted broiler breeder hens. Tanor et al (1984) reported decreased feed consumption and body weight due to shortterm heat stress and de Andrade et al (1976) reported similar results under constant, long-term heat stress in laying hens. de Andrade (1977) reported that heat stress decreased egg production and blood pCO 2 in laying hens.…”
Section: Environmental Temperaturementioning
confidence: 74%
“…Vo et al (1978) found the feed intake of Leghorn hens housed at 35°C was half of that of hens kept at 21°C. Loss of appetite has also been reported in hens subjected to heat stress, accompanied by decreases in body weight (de Andrade et al 1976 For personal use only.…”
Section: Body Weight and Feed Consumptionmentioning
confidence: 83%